The Relationship between Vitamin D Levels, Injury and Muscle Function in Adolescent Dancers - de Rezende Araújo, Iris Iasmine; Sampaio, Lucas Henrique Ferreira; Bittar, Adriano Jabur; da Silva Hamu, Tânia Cristina Dias; Wyon, Matthew Alexander; Formiga, Cibelle Kayenne Martins Roberto (International Journal of Sports Medicine, 2020)
Vitamin D has been shown to benefit a diverse range of health functions including muscle function. The aim of the present study was to identify serum 25(OH)D3 levels in a sample of adolescent dancers and compare them to muscle function and injury incidence. We incorporated a cross-sectional design to study 49 pre-professional male and female dancers (17±4.44 yrs, 52.1±6.72 kg, 1.63±0.07 m) in full-time training in Bazil. Serum 25[OH]D3 was analyzed by Enzyme-linked Immunosorbent Assay; quadriceps and hamstring peak torque and muscle fatigue were measured by isokinetic dynamometer at 60 and 300° s−1. Injury type and location in the previous 6-months were determined by self-report questionnaire. Participants were categorized into 2 groups: normal or insufficient/deficient (>or<30 ng/ml 25[OH]D3). Results indicated the normal serum 25[OH]D3 group had significantly lower fatigue rates than the insufficient/deficient group (p<0.05) but not for the other muscle function parameters. Fifty-seven percent of participants reported at least 1 injury. The most common were sprains (33%) and tendinopathies (19%). Injured dancers had significantly lower peak torque at 60°/s. The link between serum 25[OH]D3 and reduced muscle fatigue resistance has not been shown before, though the underlying mechanisms aren’t apparent and the link between muscular strength and injury has been previously evidenced.
Keywords: muscle; serum 25(oh)d; fatigue; dance; muscle strength; power